Imam Al-Ghazali Dan Perspektifnya Tentang Pentingya Pendidikan Islam - Nur hayuni; Ellya roza (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2023)
The purpose of writing this work is to describe Imam Al-Ghazali's views on the importance of Islamic education and the relevance of Imam Al-Ghazali's thoughts on Islamic education to the development of education and the demands of modern times. This study uses the literature review method to analyze Imam Al-Ghazali's perspective on the importance of Islamic education. The steps include searching for relevant sources, evaluating the reliability and credibility of sources, collecting data, qualitative analysis, and compiling a narrative that describes Imam Al-Ghazali's views on Islamic education. The results of this work are Imam Al-Ghazali's views on the importance of Islamic education a) Education directs human life towards perfection, b) Formation of noble character. The relevance of Imam Al-Ghazali's thoughts on Islamic education to the development of education and the demands of modern times a) Character and spiritual education, b) Freedom of thought and open dialogue, c) Integration of religious knowledge and values and d) preparedness in facing the challenges of modern times.